Meera’s Nature of Life and Devotion: A Study: Exploring Meera's Unique Devotional Journey (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Differentiating the devotional spirit of Meeran with contemporary organizations, Dr. Kalyan Singh Shekhawat writes in his work Biography and Poetry of Meerabai that Meeran was neither impacted by the Vallabh group nor with the Nimbarka, Sakhi, Haridasi and Radhaswami factions. In the event that there was any impact on the devotion of Meeran, it was that of Srimad Bhagavat and if any common impact can be found, it was the Five Night Tantra of the South and the Chaitanya Sampradaya of Bengal. It will be said that he acknowledged the devotion and practice rehearsed in South and Bengal, aside from the powerful devotion and practice rehearsed in North India of his era.